1982
DOI: 10.1111/j.1752-0606.1982.tb01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Let Us First Do No Harm

Abstract: This article offers the hypothesis that an increasing effort to help families and marriages may inadvertently contribute to their dysfunction. By examining the institutions of family and marriage in the broader societal perspective as well as the theories we use to assign the labels “functional” or “dysfunctional” to families and marriages, we may render a more useful service to the health of these systems. In our enthusiasm to do good, let us first do no harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…General Systems Theory upholds the importance of interpreting events, situations and people within their environment rather than in isolation (Becvar and Becvar, 1982;Von Bertalanffy, 1950, 1974Whitchurch and Constantine, 1993). From this perspective, the application of General Systems Theory to individuals involves understanding them in relation to the other people in their life.…”
Section: Fs Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…General Systems Theory upholds the importance of interpreting events, situations and people within their environment rather than in isolation (Becvar and Becvar, 1982;Von Bertalanffy, 1950, 1974Whitchurch and Constantine, 1993). From this perspective, the application of General Systems Theory to individuals involves understanding them in relation to the other people in their life.…”
Section: Fs Approachesmentioning
confidence: 99%
“…Permeability of boundaries is necessary for families to manage life events such as job changes and moving house (Seligman and Darling, 2007). Optimally functioning families develop a balance between open and closed boundaries (Becvar and Becvar, 1982;Seligman and Darling, 2007). For example, Bayat (2007) reported that the most resilient families living with ASD in their study were able to be flexible in role and responsibility changes as well as communicate with each other about personal needs.…”
Section: Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…First order changes are those that take place within the current rules and parameters governing the interaction of a family system (Becvar & Becvar, 1982). These changes do not change the structure of system dynamics.…”
Section: Theory Of Principles Of Changementioning
confidence: 99%
“…(Becvar et al, 1982). Change occurs only in behaviors as relating to and because of the defined structure of the family system (Becvar et al, 1982).…”
Section: Theory Of Principles Of Changementioning
confidence: 99%